Cerebrovascular Reserve Estimation - T. M. Ripp; E. G. Ripp; V. F. Mordovin (Общая реаниматология, 2010)
Estimation of the cerebrovascular reserve by transcranial ultrasound Doppler study on an original device and by physiological load tests may be used in cardiology, neurology, neurosurgery, and neuroreanimatology to evaluate cerebrovascular insufficiency and therapeutic effectiveness, to assess the risk for stroke, and to estimate the scope of surgery and preoper-ative preparation. Key words: cerebrovascular reserve, transcranial Doppler study, load tests.